Modification of the advertising message frame structure of the XX-XXI centuries by the example of "beer" frame - Lapshova N. V. (A new word in science: development perspectives, 2016)
the article deals with the analysis of advertising messages frame during the XX-XXI centuries. The analysis allows to highlight a typology of modifications that are found in loss or update the information about a particular quality of the goods. The dynamics of such phenomenon can be traced by the example of the frame of the XX-XXI centuries "beer".
Keywords: фрейм; слот; номинация; модификация; frame; slot; nomination; когнитивная модель; modification; cognitive model